Reframing Stakeholder Influence: A Review of Heterogeneous Stakeholder Mobilization and Corporate Responsiveness in the Era of Digital Activism - Ahembang; Agustina, Selvi (LPPM STIE Kasih Bangsa, 2026)
This qualitative literature review explores how digital activism is transforming stakeholder influence and corporate responsiveness. Contrary to traditional models emphasizing unified collective action, recent evidence reveals that heterogeneous stakeholders now mobilize through fragmented yet emotionally resonant digital narratives. This form of